780 Thousand Years of Upper‐Crustal Construction at a Melt‐Rich Segment of the Ultraslow Spreading Southwest Indian Ridge 50°28′E. Issue 10 (29th September 2021) - Chen, Jie; Cannat, Mathilde; Tao, Chunhui; Sauter, Daniel; Munschy, Marc
Abstract: Melt supply at the ultraslow‐spreading Southwest Indian Ridge (SWIR) has been shown to vary from nearly amagmatic, leading to ultramafic seafloor, to magmatically robust, producing fully volcanic seafloor. The center of the SWIR 50°28′E segment represents a magmatically robust endmember. High‐resolution bathymetry and backscatter, near‐bottom magnetic data, and visual observations were acquired to infer spatiotemporal variations in upper‐crustal construction over the past 780 kyr. Tectonic strain inferred from observed faults represents <8% of the total plate divergence during this period. Mapped seafloor and lava morphologies show a prevalence of smooth seafloor and smooth hummocky seafloor (64% mapped area), corresponding to a dominance of high‐effusion‐rate, sheet‐lobate lavas, over hummocky seafloor (29%) that mostly comprises low‐effusion‐rate pillow lavas. This prevalence is most pronounced within a ∼5 km‐long domain at the segment center, while hummocky seafloor prevails to its east and west, indicating a substantial along‐axis decrease in average eruption rate. Across‐axis changes of seafloor morphologies and faulting pattern indicate two successive cycles of upper‐crustal construction. These cycles last ∼300 kyr, interpreted as waxing and waning magmatic phases. During waxing phases, shallow axial melt lenses (AMLs) form beneath the segment center, feeding narrow diking systems that build high‐eruption‐rate smooth domal volcanos. During waning phases, lower frequencies of melt replenishment may cause the AML to become deeper and ultimately disappear. This configuration triggers diking and hummocky‐dominated eruptions over a wider axial domain, with more faults. We propose that modes of upper‐crustal construction at slow and ultraslow mid‐ocean ridges are influenced by melt supply more than spreading rate. Plain Language Summary: The ultraslow‐spreading Southwest Indian Ridge (SWIR) is characterized by extremely variable melt supply. Previous studies show that the center of the SWIR 50°28′E segment has a high melt supply with a uniquely 9.5 km‐thick crust and a crustal melt‐mush zone. Seafloor and lava morphologies, fault scarps and fissures, and eruptive units over the past 780 kyr, were mapped in this high melt supply region, using 2‐m resolution bathymetry and backscatter data collected by an autonomous underwater vehicle and seafloor photographs collected by a towed camera. Our geological mapping suggests high eruption rates and low tectonic strain, similar to intermediate‐ and fast‐spreading ridges. It also indicates that the upper crust was constructed with alternating waxing and waning magmatic phases over cycles of ∼300 kyr duration. Waxing phases are characterized by high‐eruption‐rate smooth domal volcanos fed by localized dikes. Based on available geophysical data, waxing phases occur with relatively shallow and frequently replenished axial melt lenses. By contrast, waning phases are dominated by low‐eruption‐rate hummocky ridges fed by delocalized dikes, corresponding to deeper and shorter‐lived axial melt lenses and lower frequency of melt replenishment. We propose that the upper‐crustal geology at slow‐ultraslow ridges is controlled by melt supply more than spreading rate. Key Points: The Southwest Indian Ridge at 50°28′E experienced a high eruption rate and low tectonic strain over the past 780 kyr, despite ultraslow spreading rate Seafloor and lava morphologies indicate two successive cycles of waxing and waning magmatic phases, each lasting 300 kyr Upper‐crustal construction at slow and ultraslow mid‐ocean ridges are controlled by melt supply more than spreading rate